PENGARUH LIKUIDITAS TERHADAP STRUKTUR MODAL DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING : (Studi Empiris pada Perusahaan Subsektor Kesehatan yang terdaftar di Bursa Efek Indonesia Periode 2017-2021) - Salsabila, Yulisa Rifda; Akhmadi, Akhmadi (Politeknik Negeri Ambon, 2023)
This study aims to examine the effect of liquidity on capital structure with profitability as an intervening variable. The population in this study are Health sub-sector companies listed on the Indonesia Stock Exchange in the 2017-2021 period. The number of samples in this study were 10 companies from a total of 19 populations obtained through purposive sampling method. The data analysis techniques in this study were descriptive statistics, classical assumption test, and regression analysis assisted with the SPSS 26 program. The results of this study indicate that Liquidity has no significant positive effect on capital structure, Liquidity has no significant positive effect on profitability, Profitability has no negative effect on significant to capital structure, Profitability cannot mediate the relationship between Liquidity and Capital Structure.